Information Security Practice and Experience Second International Conference, ISPEC 2006, Hangzhou, China, April 11-14, 2006, Proceedings - Chen, Kefei; Deng, Robert; Lai, Xuejia; Zhou, Jianying (Security and Cryptology, 2006)
This volume contains the Research Track proceedings of the Second Information Security Practice and Experience Conference 2006 (ISPEC 2006), which took place in Hangzhou, China, April 11-14, 2006. The inaugural ISPEC 2005 was held exactly one year earlier in Singapore. As applications of information security technologies become pervasive, issues pertaining to their deployment and operations are becoming increasingly imp- tant. ISPEC is an annual conference that brings together researchers and pr- titioners to provide a con?uence of new information security technologies, their applications and their integration with IT systems in various vertical sectors. ISPEC 2006 received 307 submissions. This is probably the highest number of paper submissions in any information security-related technical conferences. Due to this exceptionally large number of submissions and the high quality of the submitted papers, not all the papers that contained innovative ideas could be accepted. Each paper was sent to at least three Program Committee m- bers for comments. Based on the reviewers' comments and discussion by the Program Committee, of the 307 submissions, 35 were selected for inclusion in these proceedings as research track papers and another 21 papers were selected as industrial track papers and are published in the Journal of Shanghai Jiaotong University (Science).